(untitled) (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2026)
Skeletal muscle loss is often characterized as a loss of mass and strength, but simply labeling it "atrophy" doesn’t fully capture its clinical complexity. Whether it’s due to aging, chronic disease, or bed rest, the rate and severity of muscle loss vary from patient to patient. This variability demonstrates that the traditional view of protein breakdown exceeding synthesis is necessary, but not complete.